Efektivitas Pendekatan Open Ended Terhadap Kemampuan Berpikir Kreatif Matematika Siswa Kelas VI SDN 232 Tadang Palie - Firdaus; Rachman, Sidrah Afriani; Adhe Amelia Oktaviana (MACCA : Science-Edu Journal, 2025)
The research is a quantitative research wtih a pre-experimental design type one group pre-test-post-test which This research is an experimental research that aims to determine the effectiveness of the open ended approach to the creative thinking ability of mathematics grade VI students of SDN 232 tadang palie. The research design used was One Group Pretest-Posttest Design. The variables in this study were the open ended approach and the ability to think creatively in mathematics. The population in this study were all grade VI students of SDN 232 Tadang Palie with a sample of 23 students selected based on saturated sampling technique. Data collection techniques were tests, student response questionnaires, and learning implementation observation sheets. The data analysis used was descriptive and inferential statistical analysis. Based on the results of descriptive analysis, the average pretest was 40.13 and the average posttest was 74. Student response questionnaires obtained an average of 85% and the implementation of Mathematics learning with an average of 88.66%. Based on the results of the One-Sample Shapiro-Wilk Test analysis, it shows that the pretest and posttest data are normally distributed, and the Levene Statistic test results show that the pretest and posttest data are homogeneous. Based on the results of inferential statistical analysis, the value of t_count (39.528) > t_table (2.07387) is obtained, thus is rejected and is accepted. So it can be concluded that the Open Ended Approach is effectively used to improve students' mathematical creative thinking skills in class VI SDN 232 Tadang Palie.